Overview on remogliflozin SGLT-2 inhibitor in the management of type-2 diabetic mellitus in human beings - Shinde, Sagar; Avhad, Shweta; Morkar, Vidya; Patki, Chaitanya; Chikhale, Hemant; Borse, Laxmikant (Fundamental and Experimental Biology, 2023)
Sodium-glucose transport protein 2 inhibitors have become a significant category of oral medications in order to manage type 2 diabetic mellitus, particularly in people with heart disease or kidney disease, and have been highly advised overall current studies advice on how to treat. They can reduce blood pressure and help people lose weight, but they also come with drawbacks like genitourinary infections. The newly approved remogliflozin combinations are the product study of the pharmaceutical business for a new pharmaceutical class and novel drug combination with a view to managing diabetes. Remogliflozin etabonate is the term for the remogliflozin ester form. This study examines the clinical effectiveness, safety profile, pharmacokinetics, and pharmacodynamics of remogliflozin etabonate. However, itsanalytical profiling using RP-HPLC, UV, RP-UPLC, HPTLC, and LC/MS. this review addresses the individual experiments conducted during the development of analytical method for remogliflozin etabonate.